2022
DOI: 10.1097/cm9.0000000000002371
|View full text |Cite|
|
Sign up to set email alerts
|

Treatments for resectable esophageal cancer: from traditional systemic therapy to immunotherapy

Abstract: Esophageal cancer (EC) has a high incidence and poor prognosis. The two major histological types, squamous cell carcinoma and adenocarcinoma, differ in their epidemiology and treatment options. Patients with locally advanced EC benefit from multimodal therapy concepts including neoadjuvant chemotherapy, neoadjuvant chemoradiotherapy, and perioperative chemotherapy. Currently, immunotherapy for the solid tumor is a hot spot. Treatment with adjuvant immune checkpoint inhibitors (ICIs) is the first immunotherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…For patients with advanced esophageal cancer, the efficacy of traditional treatments remains unsatisfactory. 20 Immune checkpoint inhibitors (ICIs) are becoming the major means of treatment. PD-1 inhibitors exert anti-tumor effects by blocking receptor-ligand specific binding, a safe and effective treatment modality.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with advanced esophageal cancer, the efficacy of traditional treatments remains unsatisfactory. 20 Immune checkpoint inhibitors (ICIs) are becoming the major means of treatment. PD-1 inhibitors exert anti-tumor effects by blocking receptor-ligand specific binding, a safe and effective treatment modality.…”
Section: Discussionmentioning
confidence: 99%
“…ICIs are immunotherapies that target immune cell surface checkpoints and enhance immunity through the use of antibodies to ‘tumor escape’, ultimately leading to an antitumor response by turning off the immune system’s braking mechanisms. 4347 An increasing number of studies have demonstrated the efficacy and safety of ICIs in patients with ESCC. In a phase III clinical trial of advanced ESCC second-line therapy (RATIONALE-302, NCT03430843), the use of tislelizumab was associated with improved OS and better safety compared to chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic chemotherapy is the standard of care for unresectable ESCA, but patients have limited survival benefit from it, with a median overall survival of no more than 10 months [ 6 ]. Molecularly targeted therapies and immunotherapy have not yet been able to significantly improved patient survival [ 7 ]. Therefore, it is important to explore new molecules that play a key role in ESCA progression in order to develop new therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%